Noninvasive Neurally Adjusted Ventilator Assist Ventilation in the Postoperative Period Produces Better Patient-Ventilator Synchrony but Not Comfort. (22nd June 2020) - Harnisch, L. O.; Olgemoeller, U.; Mann, J.; Quintel, M.; Moerer, O.
Abstract : Background . Noninvasive neurally adjusted ventilatory assist (NAVA) has been shown to improve patient-ventilator interaction in many settings. There is still scarce data with regard to postoperative patients indicated for noninvasive ventilation (NIV) which this study elates. The purpose of this trial was to evaluate postoperative patients for synchrony and comfort in noninvasive pressure support ventilation (NIV-PSV) vs. NIV-NAVA. Methods . Twenty-two subjects received either NIV-NAVA or NIV-PSV in an object-blind, prospective, randomized, crossover fashion (observational trial). We evaluated blood gases and ventilator tracings throughout as well as comfort of ventilation at the end of each ventilation phase. Results . There was an effective reduction in ventilator delays (p < 0.001 ) and negative pressure duration in NIV-NAVA as compared to NIV-PSV (p < 0.001 ). Although we used optimized settings in NIV-PSV, explaining the overall low incidence of asynchrony, NIV-NAVA led to reductions in the NeuroSync-index (p < 0.001 ) and all types of asynchrony except for double triggering that was significantly more frequent in NIV-NAVA vs. NIV-PSV (p = 0.02 ); ineffective efforts were reduced to zero by use of NIV-NAVA. In our population of previously lung-healthy subjects, we did not find differences in blood gases and patient comfort between the two modes. Conclusion . In the postoperative setting, NIV-NAVA is well suitable for use and effective in reducing asynchronies as well as a surrogate for work of breathing. Although increased synchrony was not transferred into an increased comfort, there was an advantage with regard to patient-ventilator interaction. The trial was registered at the German clinical Trials Register (DRKS no.: DRKS00005408 ).